PA.12 Development of a dedicated breech service in a London teaching hospital. (9th June 2014) - Kidd, L; Rivers, A; George, R; Singh, N; Yentis, SM
Abstract : Since the Term breech trial, elective caesarean section (CS) rather than vaginal delivery has become standard practice for breech presentation. External cephalic version (ECV), manual rotation of the fetus from a breech to a cephalic position, is an alternative to a CS 1 and is recommended by the Royal College of Obstetricians and Gynaecologists. Anxieties about procedural pain and concerns of risks to the fetus are major reasons women decline ECV. 2, 3 In 2011, 3.8% (n = 190) of babies were breech in our hospital and only 16.3% (n = 31) of these women opted for ECV after seeing various health professionals. Different obstetricians had an overall success rate of 25.8% performing ECV. A dedicated breech service led by a specialist midwife and an obstetrician was developed in 2013 (Figure 1 ). Over the subsequent six-months, 83 women were referred to the service. Sixty women were confirmed breech at their first visit and 50 persisted as breech at their second visit. Thirty-nine women (78%) agreed to an ECV performed between 36 and 37 weeks and the ECV success rate improved to 48.6% (p < 0.05 vs pre-service using Chi-square test). Reasons for the improved uptake and success of ECV include better communication, the offer of analgesia (remifentanil) and a single operator. 83.3% of the women who had a successful ECV subsequently achieved a vaginal delivery. References: Sullivan EA, Moran K, Chapman M. Term breech singletons and caesarean section: a population study, Australia 1991-2005. Aust N Z J Obstet Gynaecol 2009;49:456–60 Rosman AN, Vlemmix F, Fleuren MAH, et al . Patients' and professionals' barriers and facilitators to external cephalic version for breech presentation at term, a qualitative analysis in the Netherlands. Midwifery May 13 2013; doi: 10.1016/j.midw.2013.03.013 Vlemmix F, Kuitert M, Bais J, et al . Patient's willingness to opt for external cephalic version. J Psychosom Obstet Gynaecol 2013;34:15–21